'I was Born in One City, but Raised in Another': Aretino's Perugian Apprenticeship. Issue 2 (22nd February 2023) - Rossiter, William T.
Abstract: According to his apocrypha, Aretino was forced to flee his hometown of Arezzo after penning some anti‐papal verses. Similarly, it is claimed that he fled Perugia ten years later after painting a lute into the hands of a depiction of the Maddalena, which stood in one of the town's piazze . Neither anecdote is true, but they point to Aretino's early reputation for both poetry and painting. In 1512, the Opera nova del fecondissimo giovene Pietro pictore Arretino was published in Venice. It was the first work by Aretino to appear in print, and the fruit of the formative time he spent in Perugia, where he was part of an urban circle of poets, artists and scholars. It was a circle and a metropolitan environment he sought to recreate in Rome and Venice. This article draws together Aretino's letters to his lifelong Perugian friends and the poems in the 1512 volume in order to examine the correspondence between their rhetorical and discursive modes. This examination shows that Perugia was the crucible of Aretino's self‐fashioning. It was in Perugia that Aretino became a poet. Where also, it would appear, he almost became a painter ( pictore ); a training that would equip him to become one of the most significant writers on art of the sixteenth century. The Opera nova shows Aretino mastering the vernacular poetic traditions available to him before, ultimately, rejecting them all in favour of himself. Perugia was the city where, with a little help from his friends, Aretino became Aretino.